EXPLORING THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A CASE STUDY OF UNIVERSITY NANI BILI NUSANTARA - Tabara, Reijeng; Jejen, La (SOSCIED, 2024)
In today’s rapidly changing and increasingly complex environment, the sustainable and contextual tasks of lecturers are important issues. Thus, this cross-sectional study investigates the impact of transformational leadership on Organizational Citizenship Behavior in higher education. Data were collected from 48 Lecturers at Nani Bili Nusantara University – Indonesia. Partial least square (PLS) was applied to analyze the proposed hypotheses. Our analysis results reveal that Transformational Leadership has a significant effect on Organizational Citizenship Behavior. Our results offer theoretical and practical implications for the development of the concepts of Transformational Leadership and Organizational Citizenship in higher education